Influence of blended cements on rate of steel corrosion in reinforced concrete structures in a marine tidal zone - Ngcotwana, Luthando (Central University of Technology, 2022)
To minimise the impact of early deterioration of reinforced concrete (RC) structures in the marine environment, blended cements made using supplementary cementitious materials (SCMs) are used. However, the physical, chemical, and mineralogical composition of these materials varies, hence, there is variation in their performance. This study therefore investigated the influence of selected SCMs on the corrosion rate of RC structures in a marine tidal zone, in correlation with some influencing parameters of reinforcement corrosion such as cover depth, oxygen availability, and concrete resistivity. This was achieved through an automated cycle change system, simulating the natural tide change in the marine tidal zone. Accordingly, three binders (100%PC, 70%PC/30%FA, and 50%PC/50%SL), 2 water to binder ratios (w/b) (0.45 and 0.65), and 2 cover depths (20 mm and 40 mm) were used to manufacture corrosion specimens. A total of 12 specimens were cast, each reinforced with one high tensile mild steel to act as an anode and 2 stainless steels (316 grade) which served the function of cathode. The corrosion specimens were exposed to a simulated marine tidal zone in the laboratory, which consisted of 6 hours of cyclic wetting with 5% NaCl solution and 6 hours of air-drying for a period of 3 months. All corrosion specimens were connected to a data logger which measured the voltage across a 100-ohm resistor between the working and counter electrodes on a weekly basis. The resulting current was calculated as the corrosion rate indicator. The results of this experimental study indicate that, at the early age of RC structures in the marine tidal zone, the rate of reinforcement corrosion is mostly influenced by the concrete quality and concrete cover depth. The increase in concrete cover depth reduced the corrosion rate of all the specimens, irrespective of the w/b. This was because of the increased travel path for chlorides and oxygen. In addition, higher cover depth prolongs the drying rate of the concrete pore structure, causing low oxygen availability, especially at low w/b, and thus low corrosion risk. Furthermore, a higher w/b 0.65 was found to increase the corrosion risk of the specimens, especially at lower cover depth. Nevertheless, due to the denser microstructure of blended cement concretes, Portland cement (PC) exhibited the highest corrosion rate. Hence, it can be inferred that high w/b can be used in the application of blended cements, provided relatively higher cover depth is used. Blended cement concretes, overall, showed relatively high concrete resistivity compared to PC concretes. In relation to the refinement of the exposure classification used in SANS guidelines, the findings of this study support the notion of adopting the classification of RC structures with a concrete cover depth ≥ 30 mm in the same category as the submerged zone. However, a further laboratory investigation over a longer period of exposure is required to further clarify the corrosion performance of blended cement concretes in a marine tidal zone.
Thesis (Master: Engineering: Civil Engineering)--Central University of Technology
Keywords: Supplementary cementitious materials (SCMs); Corrosion; Marine tidal zone; High concrete resistivity